Comparing digital image analysis and visual rating of gamma ray induced Bent grass (Agrostis stolonifera) mutants - TIWARI, AJAI KUMAR; KUMAR, RAMESH; KUMAR, GUNJEET; KADAM, GANESH B; SAHA, T N (The Indian Journal of Agricultural Sciences, 2015)
The effectiveness of digital image analysis (DIA) for determining turf quality over visual rating was judged. It provides an alternative method to measure the reflectance from vegetative surfaces and showed strong agreement with visual ratings in evaluating turf color. It is clear from the data that the correlations of hue and dark green colour index (DGCI) were significantly positive with the parameters of visual rating. There were non-significant correlation of brightness with quality and texture, and saturation and texture. The DGCI values were in line with each of these parameters when the slope of regression line was significantly different from zero (P